Hybrid business models and the public science-private industry interface - Andrew Earle; Dante I. Leyva-de la Hiz; Yusi Turell (Journal of Business Models (JOBM), 2019)
We draw on recent research in business models and hybrid organizations to propose a novel model for bridging the logics that often conflict as science-based technologies are commercialized. The key insight from this model is adopting a broader conceptualization of value creation may enhance technology commercialization efforts and outcomes.
Keywords: 650; Technology Commercialization; Hybrid Organizations; Value Creation